Production of IFN-γ and IL-4 Against Intact Catalase and Constructed Catalase Epitopes of Helicobacter pylori From T-Cells - Ghasemian Safaei, Hajieh (Jundishapur J Microbiol, 2015)
BACKGROUND: Helicobacter pylori infection is highly prevalent in the developing countries. It causes gastritis, peptic ulcer disease, and gastrocarcinoma. Treatment with drugs and antibiotics is problematic due to the following reasons: cost, resistance to antibiotics, prolonged treatment and using multiple drugs. Catalase is highly conserved among the Helicobacter species and is important to the survival of the organism. It is expressed in high amounts and is exposed to the surface of this bacterium; therefore it represents a suitable candidate vaccine antigen. OBJECTIVES: A suitable approach in H. pylori vaccinology is the administration of epitope based vaccines. Therefore the responses of T-cells (IFN-γ and IL-4 production) against the catalase of H. pylori were determined. Then the quality of the immune responses against intact catalase and three epitopes of catalase were compared. MATERIALS AND METHODS: In this study, a composition of three epitopes of the H. pylori catalase was selected based on Propred software. The effect of catalase epitopes on T-cells were assayed and immune responses identified. RESULTS: The results of IFN-γ, IL-4 production against antigens, epitopes, and recombinant catalase by T-cells were compared for better understanding of epitope efficiency. CONCLUSIONS: The current research demonstrated that epitope sequence stimulates cellular immune responses effectively. In addition, increased safety and potency as well as a reduction in time and cost were advantages of this method. Authors are going to use this sequence as a suitable vaccine candidate for further research on animal models and humans in future.